Debunking the myths of workplace fun. (16th March 2020) - Bilginoğlu, Elif
Some of the myths of workplace fun which are formed in the minds of some people either get in the way of creating a fun work environment or cause people to feel guilty or judge others, when they are having fun at work. In order to eliminate these myths, this paper explains why conclusions that appear to be 'facts' can truly be 'myths' about workplace fun. Each myth presented in this paper is followed by a discussion of related research on workplace fun and its implications for organisations, managers and employees. Thus, this paper attempts to clarify a number of issues about this concept and aims to offer a factual report which corrects the myths surrounding workplace fun by making us become more aware of what research has to say about it. A number of widely held beliefs about workplace fun are examined in the context of research findings and a literature review that demythologise them with alternative perspectives. The key to understanding that the workplace fun has positive organisational effects, than most of us have been led to believe; is to dispel these myths, so that we have a better understanding of the concept.